The Effectiveness of the Use of the Drug "Proroot MTA" in the Therapeutic and Surgical Treatment of Periodontitis - Islamova Nilufar Bustanovna; Abdulaxatov Abdugaffor Abdusattor ugli (Scientific Trends, 2024)
During the in vitro and in vivo ProRoot MTA study, compliance with the requirements for an ideal material was revealed. These properties make it possible to use ProRoot MTA for various indications. The article describes two studies devoted to the use of this material in the biological treatment of pulpitis of permanent teeth and retrograde filling of teeth with destructive periapical processes. ProRoot MTA material can be used in an outpatient clinic in various clinical situations, taking into account the indications of the use of the material.